2020
DOI: 10.1074/jbc.ra119.011946
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic Bruton's tyrosine kinase activates PLCγ2 variants mediating ibrutinib resistance in human chronic lymphocytic leukemia cells

Abstract: Treatment of patients with chronic lymphocytic leukemia (CLL) with inhibitors of Bruton's tyrosine kinase (BTK), such as ibrutinib, is limited by primary or secondary resistance to this drug. Examinations of CLL patients with late relapses while on ibrutinib, which inhibits BTK's catalytic activity, revealed several mutations in BTK, most frequently resulting in the C481S substitution, and disclosed many mutations in PLCG2, encoding phospholipase C-γ2 (PLCγ2). The PLCγ2 variants typically do not exhibit consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 106 publications
(125 reference statements)
0
24
0
Order By: Relevance
“…Varied effects of inhibitor binding on the non-catalytic functions of kinases have been observed previously and range from alterations in interactions with upstream or downstream regulatory kinases and phosphatases to changes in ligand affinity ( Sonti et al, 2018 ; Leonard et al, 2014 ; Tong et al, 2017 ; Skora et al, 2013 ). For BTK specifically, recent evidence suggests that non-catalytic functions of Ibrutinib-bound BTK activate CLL-specific PLCγ variants ( Wist et al, 2020 ). Thus, selection of BTK inhibitor type to treat specific disease states as well as design of the next generation of BTK inhibitors need to carefully consider the impact of the inhibitor on BTK regulatory domain conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varied effects of inhibitor binding on the non-catalytic functions of kinases have been observed previously and range from alterations in interactions with upstream or downstream regulatory kinases and phosphatases to changes in ligand affinity ( Sonti et al, 2018 ; Leonard et al, 2014 ; Tong et al, 2017 ; Skora et al, 2013 ). For BTK specifically, recent evidence suggests that non-catalytic functions of Ibrutinib-bound BTK activate CLL-specific PLCγ variants ( Wist et al, 2020 ). Thus, selection of BTK inhibitor type to treat specific disease states as well as design of the next generation of BTK inhibitors need to carefully consider the impact of the inhibitor on BTK regulatory domain conformation.…”
Section: Discussionmentioning
confidence: 99%
“…This conformational shift could promote kinase independent signaling events(8,64,65) and/or create a dominant negative. Varied effects of inhibitor binding on the non-catalytic functions of kinases have been observed previously and range from alterations in interactions with upstream or downstream regulatory kinases and phosphatases to changes in ligand affinity(44,45,66,67).For BTK specifically, recent evidence suggests that non-catalytic functions of Ibrutinib-bound BTK activate CLL-specific PLC variants(68). Thus, selection of BTK inhibitor type to treat specific disease states as well as design of the next generation of BTK inhibitors need to carefully consider the impact of the inhibitor on BTK regulatory domain conformation.Of the five active site inhibitors studied here only CGI1746, CC-292 and GDC-0853 inhibit kinase activity without disrupting the autoinhibitory conformation of the full-length kinase.…”
mentioning
confidence: 88%
“…In a study using genetically modified CT40 B lymphocytes, it was shown that CLL-specific mutant forms of PLCG2, including S707Y, are hyperresponsive to activated BTK even when the enzymatic activity of BTK is abrogated. 15 Because inactive BTK is insensitive to inhibition, these mutations may contribute to resistance to BTK inhibitors.…”
Section: Mechanisms Of Resistance To Targeted Therapies Secondary Mutmentioning
confidence: 99%
“…4,5 In B lymphocytes, SYK phosphorylates a signaling subunit of the BCR and activates multiple downstream targets, including PLCG2. 6,7 The protein PLCG2 is a transmembrane enzyme that catalyzes a hydrolytic reaction to activate the signaling molecules diacylgycerol (DAG) and inositol 1,4,5-triphosphate (IP3), 8,9 potentiating calcium-dependent intracellular signaling pathways. 8 PLCG2 does not ordinarily have any constitutive signaling capability, and its activity is therefore felt to be entirely dependent on, and highly sensitive to, upstream kinases such as BTK and SYK.…”
Section: Discussionmentioning
confidence: 99%
“…8 PLCG2 does not ordinarily have any constitutive signaling capability, and its activity is therefore felt to be entirely dependent on, and highly sensitive to, upstream kinases such as BTK and SYK. 9 A number of somatic variants of the PLCG2 have been associated with ibrutinib resistance. 10 The majority of these are believed to be gain-of-function mutations, permitting constitutive BCR signaling in the presence of BTK inhibition.…”
Section: Discussionmentioning
confidence: 99%